Combined treatment using cross-leg free flap and the Masquelet technique: a report of two cases - Osaki, Takeo; Hasegawa, Yasuko; Tamura, Ryosuke; Fukui, Tomoaki; Oe, Keisuke; Niikura, Takahiro; Nomura, Tadashi; Hashikawa, Kazunobu; Terashi, Hiroto (Case reports in plastic surgery and hand surgery, 2022)
We introduce a treatment that combines the cross-leg free flap with the Masquelet technique and describe two cases using this method for bone and soft tissue reconstruction. Both patients were successfully treated and ambulatory. This novel method can be safely performed using the delay technique, indocyanine-green angiography and near-infrared spectroscopy.